Search for long-lived heavy neutral leptons with displaced vertices in proton-proton collisions at √s = 13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Journal of high energy physics)
A search for heavy neutral leptons (HNLs), the right-handed Dirac or Majorana neutrinos, is performed in final states with three charged leptons (electrons or muons) using proton-proton collision data collected by the CMS experiment at root s = 13 TeV at the CERN LHC. The data correspond to an integrated luminosity of 138 fb(-1). The HNLs could be produced through mixing with standard model neutrinos v. For small values of the HNL mass (<20 GeV) and the square of the HNL-v mixing parameter (10(-7)-10(-2)), the decay length of these particles can be large enough so that the secondary vertex of the HNL decay can be resolved with the CMS silicon tracker. The selected final state consists of one lepton emerging from the primary proton-proton collision vertex, and two leptons forming a displaced, secondary vertex. No significant deviations from the standard model expectations are observed, and constraints are obtained on the HNL mass and coupling strength parameters, excluding previously unexplored regions of parameter space in the mass range 1-20 GeV and squared mixing parameter values as low as 10(-7).